The principal's supervision in evaluating teacher performance programs at MIS Al-Hikmah Namorambe - Mukhlasin, Ahmad; Syahrin, Mhd Alfi; Siagian, Indra Sakti; Hirwansyah, Hirwansyah (International Journal of Trends in Mathematics Education Research, 2024)
This study aims to describe the stages of principal supervision in evaluating teacher performance at MIS Al-Hikmah Namorambe and describe the obstacles to principal supervision in evaluating teacher performance at MIS Al-Hikmah Namorambe. The research method used is qualitative with a descriptive qualitative approach. The data collection techniques used are observation, interviews and documentation. While data analysis techniques in the form of data reduction, data presentation and data conclusion. The results showed that First, the planning carried out by the principal includes identifying problems based on the objectives of supervision, determining the supervision schedule, selecting supervision techniques that are in accordance with the needs of teachers, and preparing assessment instruments for observation. Second, implementation, which is the process of supervision activities, where principals check the completeness of learning tools, observe the learning process, and conduct assessments based on observation instruments. Third, analysis, where the principal identifies teacher weaknesses based on the observation results. Fourth, follow-up which includes providing solutions to teachers who do not meet the standards and giving awards to teachers who meet the standards. Finally, the preparation of a report by the principal as a guideline for the implementation of supervision in the future, as for the obstacles faced by principals and teachers in implementing this supervision is time management.